DESAIN DAN KAJIAN SIMULATIF HEAT EXCHANGER BERPROFIL ‘SPIRAL TUBE IN PIPE’ SEBAGAI PEMINDAH PANAS ANTARA ETHANOL DAN AIR - Lapisa, Remon; Fernandez, Donny; Putra, Dwi Sudarno (Sainstek, 2009)
The energy crisis has stimulated scientists to begin developing the concept of zero energy building through residual energy conservation and turn it into something useful, One of them is the use of ethanol in PEM fuel cells are obtained through distillation. To change the temperature Ethanol and can be destilled, will be designed heat exchanger that has a function : raising the temperature of ethanol in order to evaporates with intermediate high temperature water, and then lowering the temperature back pure ethanol with low-temperature water heat convection. ‘Spiral Tube In Pipe’heat exchanger is designed to transfer heat that brought by ethanol with the temperature  80 C  to the cooling water in a spiral tube wrapped with a pipe. Hopefully, through this method can achieve maximum heat transfer value, with low cost on ethanol output temperature 35 C. The basic principles in the development of this heat exchanger are the achievement of maximum heat transfer, Simple in design  and economic value.Tube material made of copper wich has good conduction coefficient. Water pipes made ​​of PVC plastic gutter is easily available and cheap. Minimum pipe size is designed to be more flexible, easily placed anywhere and is simple to maintain. In this paper also included a CFD simulation to determine the flow characteristics that occur along the copper tube. Mathematical equations of physical phenomena was resolved through a linear regression methods. Keywords: heat transfer, Spiral tube , efficiency, CFD simulation